The Analytical Framework of Governance in Health Policies in the Face of Health Emergencies: A Systematic Review - Díaz-Castro, Lina; Ramírez-Rojas, María Guadalupe; Cabello-Rangel, Héctor; Sánchez-Osorio, Ever; Velázquez-Posada, Mauricio (Frontiers in Public Health, 2022)
The Governance Analytical Framework (MAG) defines governance as a social fact, endowed with analyzable and interpretable characteristics, through what it calls observable constitutive elements of governance: the problem, the actors, the social norms, the process of decision-making and scope or nodal points; in the sense that each society develops its modes of governance, its decision-making or conflict resolution systems among its members, its norms, and institutions. In this perspective, the purpose of this article was to carry out a systematic review of the scientific literature to understand the role of governance in health policies in health emergencies, such as that caused by the SARS-CoV-2. The systematic review was designed based on the methodology proposed in the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) Declaration. The literature search was carried out in six databases: Psychology and Behavioral Sciences, APA-PsycInfo, MEDLINE, eBook Collection (EBSCOhost), PubMED, and MedicLatina, published in the last five years. Fifteen articles that met quality and evidence criteria were analyzed. The governance approach alluding to the health emergency problem in health policies was the most addressed by the authors (80%), followed by a description of the actors (40%), the process of decision-making spaces (33%), and ultimately, social norms or rules with 13%. Formulating a coherent set of global health policies within a large-scale global governance framework is mostly absent. Although the countries adopt international approaches, it is a process differentiated by the social, economic, and political contexts between countries, affecting heterogeneous health outcomes over the pandemic.